O tempo do processo: os processos judiciais envolvendo a educação no Poder Judiciário de Minas Gerais - Cusciano, Dalton Tria (2011)
This study aims to measure the duration of court cases involving education social rights, seeing how this time affects the enjoyment of those rights. In order to achieve such objectives I identified and analyzed the legal cases, since its entry in a state court until the date of the trial session of Court of Appeals of Minas Gerais. Subsidiary this work also identified who the litigants are, the influence of granting injunctions in the duration of the processes, the time variation of the process based on the location of the county in which the process begins and the existence of dead steps in court proceedings. The assumption that guided the study is the possibility of extinction of certain rights, such as the right of places in day care and the right to access public higher education free of charge, in face of an excessive length of time of the lawsuit.